A COMPARATIVE STUDY OF ABU NASR MUHAMMAD FARABI’S “UTOPIA” WITH DAVID HARVEY’S “RIGHT TO THE CITY” - Farajian, Morteza (Revista Gênero e Interdisciplinaridade, 2022)
The aim of the present study is a comparative study of Farabi and Harvey’s theoretical apparatus about their ideal city. The method of this research is theoretical comparison using content analysis method. According to the theoretical framework and dimensions of the research methodology of the theoretical system, in this section, the views of Farabi and Harvey are compared. The research results show that Farabi’s theoretical metaphor is organic and Harvey’s metaphor is construction (infrastructure and superstructure). Farabi also uses the exponential method to explain the ideal city, but Harvey uses the dialectical method. Farabi sees the ideal city as having an orderly hierarchy but a class-military Harvey with conflict. Farabi proposes help and cooperation as a way to prosperity in the city, but Harvey proposes focused global movements to achieve the right of the city, and awaits “moments of creative destruction.” Finally, the results showed that there is a fundamental difference between the utopia of Farabi and Hawari, one that emphasizes order, stability, hierarchy and the other on conflict, change and expropriation.